2005
DOI: 10.1080/01443610500328306
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sexual practices and responses among ante-natal clinic attendees in a Nigerian teaching hospital

Abstract: A cross-sectional study was carried out among 134 antenatal clinic attendees in a Nigerian tertiary hospital to assess pregnancy-related sexual beliefs and changes in sexual frequency and response. Information was collected through a semi-structured questionnaire, and analysed by SPSS. Only 15% of women believed that religious, social or cultural reasons prevented sexual intercourse in pregnancy. Frequency of sexual intercourse decreased in pregnancy in 37.4% of the respondents, remained unaltered in 46.1% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…However, it must be recognized with Von Sydow [15] that the male partner is not taken into account in most studies. As emphasized by many authors [9,16] and reported by women in our study, there is a decrease in the pleasure of sexual intercourse and even desire during pregnancy. Despite the lack of pleasure generated by the sexual act, the majority of women in this study are engaged in it, in fact, to satisfy or retain the partner as pointed out by some authors [10,11,14].…”
Section: Sexuality During Pregnancysupporting
confidence: 73%
“…However, it must be recognized with Von Sydow [15] that the male partner is not taken into account in most studies. As emphasized by many authors [9,16] and reported by women in our study, there is a decrease in the pleasure of sexual intercourse and even desire during pregnancy. Despite the lack of pleasure generated by the sexual act, the majority of women in this study are engaged in it, in fact, to satisfy or retain the partner as pointed out by some authors [10,11,14].…”
Section: Sexuality During Pregnancysupporting
confidence: 73%
“…A meta-analysis study conducted by von Sydow demonstrated that sexual intercourse frequency did not significantly change during the first and the second trimesters, however, it decreased significantly during the third trimester (19). Moreover, Hart et al, Adeyemi et al, and Erenel et al found a gradual decline in vaginal intercourse in their studies (34,36,50).…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, the rate was not investigated in the first trimester, but decreased from the first to the second trimester, as previously reported. Eight studies compared the SI rate before and after pregnancy (Table 3) [33][34][35]37,[40][41][42][43]. The rate increased in 6.7 (0.7-16.5)% cases, decreased in 75.3 (37.4-99.3)%, and remained unchanged in 21.2 (0-46.1)%.…”
Section: Systematic Review On Sexual Intercourse During Pregnancymentioning
confidence: 99%